Relationship Between Clinical Factors of Lymphoma DLBCL GCB and Non-GCB Subtype with Ki-67 Proliferation Index in Siloam Karawaci Hospital 2014 - 2018 - Kristiani, Erna; Marisca, Stephanie; Qurro, Tri Ulfatul; Kweeswara, Natasya; Chandra, Amos Immanuel (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: Non-Hodgkin large cell B-lymphoma (DLBCL: Diffuse Large B-cell Lymphoma) were classified into two subtypes of Germinal Center B-Cell Like (GCB) and non-Germinal Center B-Cell Like (non-GCB), which GCB has a better prognosis. The Ki-67 antigen is one of the most reliable markers of cell proliferation. This research aims to establish the relationship between proliferation index Ki-67 with DLBCL subtypes and to evaluate the utility of Ki-67 proliferative index as a predictive marker for predicting stages of lymphoma.Methods: We obtained 60 cases of patient samples DLBCL in Siloam Hospital Lippo Karawaci in 2014-2018. Clinical and pathological data were obtained from medical records. Chi-square methods were used to analyze data.Result: There were more ≤60 years compared to >60 years. In this study, there were more male patients than female patients. lymphoma provided in extranodal were higher than lymphoma in nodal form.Conclusions: There is a relationship between Ki-67 proliferation index with lymphoma GCB and non-GCB subtypes and stage of lymphoma, which can be used as a predictive factor in predicting the stage of lymphoma.